A new geography of innovation – China and India rising - Gert Bruche (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective explains the factors behind the sudden shift toward China and India for MNE R&D centers and explores how the financial crisis will affect China's and India's ability to continue to capture the R&D market.
Keywords: 330